The Daily Nadeem, Bhopal : His Highness the ruler of Bhopal's (1939) birthday souvenir number : an illustrated account of birthday celebrations - Hamidullah Khan, Mohammed, Nawab of Bhopal, 1894-1960 (Maḥmūdulḥasan Ṣiddīqī, 1939)
Poems, short stories, articles, etc., in honor of the late ruler of Bhopal State, Mohammed Hamidullah Khan, Nawab of Bhopal, 1894-1960; special number of Rozānah Nadīm, Urdu daily newspaper.